Ramifications of Artificial Intelligence and Cyber Security - V Hans (International Journal of Information Security Engineering, 2025)
Artificial intelligence (AI) has pros and cons for cyber security: AI can improve network security, anti-malware, and fraud detection. AI can simulate cyberattacks, automate responses, and analyse enormous databases. AI-powered phishing and deepfakes are cyber risks. AI can potentially be attacked and become a liability for corporations. AI has transformed cyber security, bringing both new opportunities and challenges. AI-powered tools discover abnormalities faster, automate threat responses, and improve threat detection accuracy. As AI systems improve, fraudsters use them to launch complex attacks like AI-generated phishing schemes, deepfakes, and adaptive malware. Defenders must innovate to outperform hostile actors in this cyber arms race due to AI's dual usage. This article discusses how AI integration in cyber security might minimize or increase cyber threats and the ethical and regulatory frameworks needed to handle this changing situation. AI algorithms can find software trends and spot basic infections and ransomware before they infect computers. AI can boost capabilities and protect data by reviewing articles, news updates, and cyber risk research using natural language processing.
Keywords: AI-driven attacks; Artificial Intelligence (AI); Automation; Cyber security; ethics; threat detection